Help Preferences Among Employees Who Wish to Change Health Behaviors. (August 2014) - Persson, Roger; Cleal, Bryan; Jakobsen, Mette Øllgaard; Villadsen, Ebbe; Andersen, Lars L.
Objective . To examine the help preferences of employees in the Danish police who had acknowledged that they wished to change health behaviors. In addition, we explored whether preferences varied with age, gender, chronic health concerns, positive expectations of good health, and past experiences of in-house health promotion services (i.e., wellness service). Methods. Respondents to an electronic questionnaire who acknowledged wishing to change health behaviors in relation to smoking ( n = 845), alcohol ( n = 684), eating ( n = 4, 431), and physical activity ( n = 5, 179) were asked to choose up to three help alternatives on a predefined list. Results. In descending order, smokers preferred help from nicotine gum, no help, and help and support from family and friends. Alcohol consumers preferred no help or help and support from family and friends or "other" forms. Employees who wanted to change eating habits preferred a free fruit bowl, free nutritional guidance, and healthy food at work. Employees who wanted to change physical activity patterns preferred exercise at work, offers of free exercise, and exercise in a social/collegial context. Conclusion. Wishing to change health behaviors is not always accompanied by perceiving a need for assistance. The no-help option was selected fairly frequently and mostly in relation to alcohol and smoking. A fruit bowl was the most preferred option for help, followed by exercise at work and free exercise. Help from traditional health services was ranked low, possibly reflecting that they are primarily viewed as a solution for stopping disease rather than promoting health.